2005
DOI: 10.1128/mcb.25.13.5648-5663.2005
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Methylation Provides Epigenetic Transcription Memory for Retinoid-Induced Differentiation in Myeloid Cells

Abstract: Cellular differentiation is governed by changes in gene expression, but at the same time, a cell's identity needs to be maintained through multiple cell divisions during maturation. In myeloid cell lines, retinoids induce gene expression and a well-characterized two-step lineage-specific differentiation. To identify mechanisms that contribute to cellular transcriptional memory, we analyzed the epigenetic changes taking place on regulatory regions of tissue transglutaminase, a gene whose expression is tightly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 61 publications
(55 reference statements)
2
44
0
Order By: Relevance
“…The role of PRMTs in hematopoiesis, specifically in myeloid differentiation, was highlighted by Balint et al (2005a, b), who demonstrated the methylation of H4R3 'primes', the regulatory region of specific genes for RAinduced myeloid differentiation (Balint et al, 2005b). Treatment of HL60 myeloid leukemia cells with vitamin D or dimethyl sulfoxide induced a 'precommitment' state that was linked to a rapid decrease in promoter H3K4 methylation and an increase in enhancer H4R3 methylation of the tissue transglutaminase gene, whose expression is linked to RA-induced differentiation.…”
Section: Protein Arginine Methyltransferasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of PRMTs in hematopoiesis, specifically in myeloid differentiation, was highlighted by Balint et al (2005a, b), who demonstrated the methylation of H4R3 'primes', the regulatory region of specific genes for RAinduced myeloid differentiation (Balint et al, 2005b). Treatment of HL60 myeloid leukemia cells with vitamin D or dimethyl sulfoxide induced a 'precommitment' state that was linked to a rapid decrease in promoter H3K4 methylation and an increase in enhancer H4R3 methylation of the tissue transglutaminase gene, whose expression is linked to RA-induced differentiation.…”
Section: Protein Arginine Methyltransferasesmentioning
confidence: 99%
“…Treatment of HL60 myeloid leukemia cells with vitamin D or dimethyl sulfoxide induced a 'precommitment' state that was linked to a rapid decrease in promoter H3K4 methylation and an increase in enhancer H4R3 methylation of the tissue transglutaminase gene, whose expression is linked to RA-induced differentiation. These 'primed' cells were then treated with RA, resulting in H4 acetylation and H3K4 methylation and transcriptional activation (Balint et al, 2005b). Also implicated in this chain of events is the enzyme peptidyl arginine deiminase, PAD4, which removes the methyl mark on H4R3, and is also associated with RA-induced gene activation .…”
Section: Protein Arginine Methyltransferasesmentioning
confidence: 99%
“…Accordingly, extensive large scale efforts have aimed to identify arginine methylated proteins (23)(24)(25). Based on these and other studies, arginine methylation appears to impact a variety of cellular processes including ribosome biosynthesis (26), T-cell activation (27), cytokine and interferon signaling (28), cell differentiation (29), and DNA repair (30). The role of arginine methylation in these cellular pathways is likely regulated by biochemical activities such as protein-protein interactions (31,32), protein subcellular localization (33,34), transcription and chromatin remodeling (35,36), mRNA metabolism (37,38), and translation (26,39).…”
mentioning
confidence: 99%
“…Therefore, we established transient overexpression of wild-type PRMT1 (WT) and the catalytically inactive PRMT1 mutant XGX (Balint et al 2005), which were equally well expressed (Fig. 4A).…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…The following plasmids were used: pcDNA3.1-PRMT1 wild-type and pcDNA3.1-PRMT1-Myc XGX mutant were published recently (Balint et al 2005). pGex2T-GAR and pGex2T-PRMT3 were described previously (Tang et al 1998).…”
Section: Plasmidsmentioning
confidence: 99%